Quality adjusted price indexes for discrete goods - John K. Dagsvik; Astrid L. Mathiassen; Bengt J.Eriksson (Statistics Norway, Research Department, 2006)
This paper discusses the construction and computation of a quality adjusted price index when the commodities are differentiated products, such as different brands of automobiles and refrigerators. The method we focus on is an extension of Trajtenberg's approach. A key result obtained in the paper is that the evolution of the quality adjusted price index depends crucially on the fraction of consumers that do not purchase a variant of the product. The method is applied to data on automobile demand in Norway from 1994 to 2002. Both the Laspeyres index and the index based on hedonic regression yield lower estimates of the pricees from 1999 to 2002 than does the quality adjusted price index. This is mainly due to variations in the fraction of persons who purchase new automobiles.
Keywords: C25; C43; 330; Quality adjusted price index; Exact index theory; Hedonic price indexes